The artist as innovation muse: Findings from a residence program in the fuzzy front end - Berit Sandberg (Administrative Sciences, 2020)
In a highly competitive business environment, integrating artists into corporate research and development (R&D) seems to be a promising way to foster inventiveness and idea generation. Given the importance of individual level innovation for product development, this study explores the benefits that employees experience from the artist-in-residence-program at Robert Bosch GmbH, Germany. Qualitative content analysis of interviews with scientists and engineers was performed in order to explore the impact of their encounters with artists in the theoretical framework of the triadic concept and transmission model of inspiration. The findings corroborate the notion that inspiration is a suitable theoretical underpinning for individual benefits of art-science collaborations in the front end of innovation. Scientists and engineers are inspired by the artists' otherness and transcend their usual modes of perception in favor of enhanced focal, peripheral and bifocal vision. Whereas shifts in perspective are reflected in individual thinking patterns, researchers are hardly motivated to change their work-related behavior. The exchange with artists does not have a concrete impact on technological innovation, because researchers neither integrate impulses into their experiential world nor link them to fields of activity. In the case under scrutiny, artistic impulses do not contribute to idea generation in the sense of front-end activities. The study contributes to research on artists in businesses by illuminating the R&D environment as a hitherto neglected field of activity. While substantiating previous research on artist-in-science-residencies, the results suggest that the potential of such interdisciplinary endeavors is limited.
Keywords: 350; artist-in-residence; artist-in-science-residency; art-science collaboration; front end ofinnovation; innovation; inspiration; research and development